2019
DOI: 10.1016/j.cjtee.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of massive transfusion in trauma patients in the surgical intensive care units (THAI-SICU study)

Abstract: Purpose After damage control surgery, trauma patients are transferred to intensive care units to restore the physiology. During this period, massive transfusion might be required for ongoing bleeding and coagulopathy. This research aimed to identify predictors of massive blood transfusion in the surgical intensive care units (SICUs). Methods This is an analysis of the THAI-SICU study which was a prospective cohort that was done in the 9-university-based SICUs in Thailan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In the present study, the incidence of MBT was 3.9%, concordant with prior studies that have been reported in a range from 1.8% to 5.0%. [ 1 - 3 ] MBT can occur unexpectedly as an event, which is important to consider because such an event significantly increased mortality in the present study. This finding is similar to what was previously shown in a study by O’Keeffe et al ., which demonstrated that MBT was significantly associated with 30-day mortality.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In the present study, the incidence of MBT was 3.9%, concordant with prior studies that have been reported in a range from 1.8% to 5.0%. [ 1 - 3 ] MBT can occur unexpectedly as an event, which is important to consider because such an event significantly increased mortality in the present study. This finding is similar to what was previously shown in a study by O’Keeffe et al ., which demonstrated that MBT was significantly associated with 30-day mortality.…”
Section: Discussionmentioning
confidence: 77%
“…Massive blood transfusion (MBT) occurs in several situations including for severely injured trauma victims, [ 1 ] uncontrolled blood loss, [ 2 , 3 ] and intraoperative incidental injury to major vessels. [ 4 ] The incidence of MBT ranges from 1.8% to 5.0%, [ 1 - 3 ] and the common situations that lead to MBT include trauma, cardiac surgery, liver transplantation, ruptured abdominal aortic aneurysm, gastrointestinal hemorrhage, and postpartum hemorrhage. [ 2 , 3 ] However, the association between MBT and mortality remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…28 Several scoring systems have been developed to predict the need for MBT, including the ABC score, which takes into account the penetrating mechanism, ED SBP, ED HR, and a positive Focused Assessment with Sonography for Trauma (FAST) exam, as well as the MBTT score, which is calculated based on age (>60 years), BE (<−10 mEq/L), lactate (>4 mmol/L), and HR (>105/min) or SOFA score (>9). [29][30][31] Other indicators, such as the shock index at ED arrival, can indicate hypovolemic shock and the likelihood of requiring transfusion. 17 In the study by Koch et al, shock index was shown to be a good predictor, where a shock index >0.9-1.1 could predict massive blood transfusion with an RR of 1.61 (95% CI: 1.13-2.31) but could not predict ICU admission and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms may include the fact that SOFA scores are more likely to indicate liver failure or cardiovascular failure. Those organ failures have a high tendency to bleed, and subsequently leading to coagulopathy (26).…”
Section: Discussionmentioning
confidence: 99%